The Basic Idea of the Attentat Clause in Terrorism Related Criminal Offenses - Sunardi; Akbar, Rizki; Bastomi, Ahmad; Kaimudin, Arfan (Jurnal Suara Hukum, 2026)
The application of the attentat clause in terrorism-related crimes mainly emerges in extradition proceedings, where perpetrators often invoke political motives to avoid surrender under the political offense exception, thereby hindering international cooperation. Essentially, the attentat clause affirms that murder or attempted murder of a head of state or other protected persons cannot be classified as political crimes, but rather as serious ordinary crimes with transnational implications. This study examines the legal implications of divergent national regulations on the attentat clause in the extradition of terrorism offenders, with particular attention to human rights protection. Employing a normative juridical method through statutory and comparative approaches, the research is supported by literature review and analysis of relevant legal materials. The findings show that Indonesia’s regulation of the attentat clause is broadly aligned with international legal principles that recognize terrorism as a universal crime and reject the political offense exception. However, discrepancies between Indonesia’s legal framework and those of several other states may generate legal uncertainty and weaken Indonesia’s effectiveness and bargaining position in extradition processes. The novelty of this research lies in integrating the core concept of the attentat clause with comparative analysis and its practical implications for extradition, while emphasizing human rights considerations. Accordingly, harmonization between the Terrorism Law and the Extradition Law concerning the attentat clause is necessary to ensure legal certainty and uphold human rights in extradition proceedings.